(3GdfUjMI GdTajbI aj HjGf GdTQjYI hGdWQjbI hGdMbjbIs - (3fhQ Gdjf GdHYdjs
(3ChdgG (B:s
(3GdMeO ddg GdcQje GdaJGM hHYO JPcQGJ eY HYV GdGNhGf GdUGObjf ai JYQja GdTQjYI GdaUd GdChd ai HjGf GdTQjYI hGdWQjbI hGdMbjbI s
(3BNQgG (B:s
(3GfJgi SaQ GdWGdHjf Edi GdXaQ HbQHge aEPG XaQhG abO hUdhG GdbQH hGdHYO GdChd eG bQH ef WGYJg HeRjO YfGjJg hGdMeO ddg Ydi cd MGd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B653s
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9276) s
Keywords: (3GdJhMjO hGdedd hGdfMds